2014
DOI: 10.1016/j.cortex.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Different impressions of other agents obtained through social interaction uniquely modulate dorsal and ventral pathway activities in the social human brain

Abstract: Internal (neuronal) representations in the brain are modified by our experiences, and this phenomenon is not unique to sensory and motor systems. Here, we show that different impressions obtained through social interaction with a variety of agents uniquely modulate activity of dorsal and ventral pathways of the brain network that mediates human social behavior. We scanned brain activity with functional magnetic resonance imaging (fMRI) in 16 healthy volunteers when they performed a simple matching-pennies game… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 47 publications
3
61
0
Order By: Relevance
“…Different regions in the TPJ are also found to serve somewhat different theory-of-mind functions. Takahashi et al (2014) found that the dorsal aspect of the TPJ is related to judging how much an agent has mental functions, while the ventral aspect of the TPJ is related to judging the intelligence of an agent.…”
Section: A Neural System For Theory Of Mindmentioning
confidence: 99%
“…Different regions in the TPJ are also found to serve somewhat different theory-of-mind functions. Takahashi et al (2014) found that the dorsal aspect of the TPJ is related to judging how much an agent has mental functions, while the ventral aspect of the TPJ is related to judging the intelligence of an agent.…”
Section: A Neural System For Theory Of Mindmentioning
confidence: 99%
“…On the basis of previous studies (Lee et al, 2004; Seo and Lee, 2008; Baek et al, 2013; Takahashi et al, 2013, 2014), we quantitatively represented the degree of exploration by using entropy, which is a concept in information theory (Shannon, 1948). Specifically, we calculated the conditional entropy representing the degree of dependence on the immediately previous outcomes in choices of options.…”
Section: Introductionmentioning
confidence: 99%
“…6. fMRI of brain regions where activities were modulated by "mind-holderness" (red) and "mind-readerness" (blue) (Takahashi et al, 2014). (For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.)…”
Section: Discussionmentioning
confidence: 99%
“…The x-axis indicates "mind-holderness," and the y-axis indicates "mind-readerness" (see text). The score of PCA components for each opponent represents the mean value for all participants (Takahashi et al, 2014). and network structure are far from our current understanding.…”
Section: Social Behavior Analysismentioning
confidence: 99%
See 1 more Smart Citation